6th Annual Fresno County Young Lawyers Association Justice Hopper Memorial Luncheon; Speaker: San Francisco Superior Court Judge Ira Brown - Watkins, Howard::::::::: (1987)
Front: Ellen Jahn, Grace Hopper, Angel Hopper, Larry Salinas holding baby Amber Salinas, Robin Hopper Salinas; Back: Don Boyd, Judge Ira Brown, Justice Donald Franson and Howard Sagaser Don Boyd was Grace Hopper's companion